Hypertriglyceridemia Induced Acute Pancreatitis Caused by a Novel LIPC Gene Variant in a Pediatric Patient - Laura Balanescu; Ancuta Cardoneanu; Gabriel Stanciu; Radu Balanescu; Cristian Minulescu; Daniela Pacurar; Andreea Moga (MDPI AG, 2022)
Hypertriglyceridemia induced acute pancreatitis is a rare cause of pancreatitis in children. Hepatic lipase deficiency is an extremely rare cause of hypertriglyceridemia, reported in only a few families to date. Hepatic lipase is the enzyme involved in the hydrolysis of triglycerides and phospholipids in remnants of triglyceride-rich lipoproteins that have a role in the conversion of very low density lipoprotein remnants to low density lipoproteins. Hepatic lipase deficiency is inherited in an autosomal recessive pattern. Detection of heterozygous carriers of hepatic lipase mutations remains accidental at the population level, as affected persons with a heterozygous state of hepatic lipase mutation do not display specific lipoprotein abnormalities and also patients with complete hepatic lipase deficiency have inconstant phenotype. The proximal promoter of the LIPC gene consists of four polymorphic sites in complete linkage disequilibrium. Five missense mutations in encoding exons have been described and proved to be responsible for hepatic lipase deficiency to date: S267F, T383M, L334F, A174T, and R186H, affecting the activity and secretion of hepatic lipase. We identified a primary disorder of the lipid metabolism as the cause of the acute episode of pancreatitis in a four years old patient, consisting of hepatic lipase deficiency caused by a novel genetic variant of the LIPC gene, a gross deletion of the genomic region encompassing exon 1. This variant was not previously described in the literature in persons with LIPC-related disorders and its significance is currently uncertain, but in the presented clinical and paraclinical context, it has the characteristics of a pathological variant inducing a hepatic lipase deficiency phenotype.